Analysis of Competency and Compensation on Employee Performance with Work Motivation as a Mediating Variable at the Medan Equipment Safety And Health Center and Health Facilities In Medan - Yunita Nursyahmi; Erwansyah Erwansyah; Husni Muharram Ritonga (Universitas Dehasen Bengkulu, 2026)
Employee performance is a crucial factor in ensuring the effectiveness of supervision and security of medical equipment and facilities that directly impact public safety. This study aims to analyze the effect of competence and compensation on employee performance with work motivation as a mediating variable at the Medical Equipment and Facility Security Center (BPAFK) in Medan. This study uses a quantitative approach with a census method on 81 employees. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS) with the help of SmartPLS software. The results showed that competence had a positive and significant effect on employee performance and work motivation. Compensation had a positive but insignificant effect on employee performance, but had a positive and significant effect on work motivation. Work motivation was found to have a positive and significant effect on employee performance. The indirect effect test showed that work motivation was able to significantly mediate the effect of competency on employee performance, but was not able to mediate the effect of compensation on employee performance. These findings indicate that improving the performance of BPAFK Medan employees is more effectively achieved by strengthening employee competency supported by work motivation, while compensation plays a greater role as a motivator than as a direct factor in improving performance. This study is expected to serve as a basis for BPAFK Medan leaders in formulating human resource development policies that are oriented towards the continuous improvement of employee competence, motivation, and performance